Pengaruh Customer Experience, dan Customer Trust, Terhadap Kepuasan Konsumen Menggunakan Uang Aplikasi (E-Money) Dana - Devi, Nabila; Hadian, Arief; Yuliana, Yayuk; Harahap, Nur’ain; Fikri, Muhammad Hilman (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of customer experience variables and customer trust variables on consumer satisfaction in the context of the use of money for community study fund applications in the Medan Amplas sub-district. It is recommended that future research should consider expanding the respondent pool to include individuals from various locations, as there are numerous users of this digital wallet. This research utilizes quantitative methods with a questionnaire-based research design, involving 97 respondents in the Medan Amplas sub-district. Data collection techniques encompass observation, questionnaires, and documentation, while data analysis employs validity, reliability, and classical assumption tests. The data analysis method involves multiple linear regression using the SPSS 20 program. The t-test results demonstrate that both the customer experience variable and the customer trust variable influence consumer satisfaction when using Dana e-money. The F-test results show that the customer experience variable and the customer trust variable simultaneously affect consumer satisfaction among those using Dana e-money in the Medan Amplas sub-district, as indicated by the calculated F-value exceeding the critical F-table value. The adjusted coefficient of determination (R Square) indicates that 32.4% of the dependent variable can be explained by the independent variables, while the remaining 67.6% is attributable to other variables not examined in this study.